Hubungan antara Neraca Air Lahan dan Produksi Karet Klon PB260 - . Sahuri (Jurnal Ilmu Pertanian Indonesia, 2018)
In general, rubber production was influenced by fluctuation of monthly rainfall rate. This research was aimed to determine the effect of rainfall, evapotranspiration, and soil water content on the production of PB260 rubber clone. This research was conducted at Sembawa Research Centre Experimental Field, South Sumatera from the year 2013-2016. The observed rubber tree was mature PB260 clone planted on clay loam soil. Rubber productions on the dry and rainy season on 2013-2016 were compared to determine the effect of rainfall on rubber production. The results showed that soil water content has the closest relationship to rubber production compared to rainfall and evapotranspiration parameter. Latex yield was decreasing as the decrease of soil water content at dry season. Limited water during the dry season became a constraint of optimum rubber yield. When soil water content drops below 100 mm, the maximum attained latex yield was 18 g/t/t.